Relationship between smartphone addiction and eating disorders and lifestyle among Chinese college students - Wang, Jun; Hao, Qing-Hong; Peng, Wei; Tu, Yang; Zhang, Lan; Zhu, Tian-Min (Frontiers in Public Health, 2023)
Purpose Smartphone addiction has been a matter of serious concern among society and parents because of its high incidence and serious negative effects. This study aimed to determine the association between smartphone addiction and eating disorders and lifestyle changes among college students. Methods The present article is a descriptive, cross-sectional study involving 1,112 college students from several universities in Chengdu, China. The data were collected by using the Chinese version of the Mobile Phone Addiction Index (MPAI) and the Eating Attitudes Test-26 (EAT-26). In addition, the information on sociodemographic, lifestyle, and smartphone use were obtained through a self-administered questionnaire. Results The prevalence of smartphone addiction among the students involved in the study was 22.6%, of which 10.4% were at risk for eating disorders. Female students had higher MPAI scores and EAT-26 scores than male students (p < 0.001). The proportion of male students with a risk of eating disorders was significantly higher than that of female students (p < 0.05). The total EAT-26 scores of students with smartphone addiction were higher than that of others (p < 0.001). The correlation analysis indicated that the MPAI scores were significantly positively correlated with the EAT-26 scores, depression and anxiety, difficulty in falling asleep at night, the frequency of eating fast food and drinking carbonated soft drink (p < 0.01). In addition, the MPAI scores were significantly negatively correlated with skipping breakfast and the frequency of physical activity (p < 0.05). Conclusion Smartphone addiction is significantly associated with eating disorders, eating habits, and lifestyle. The influence of dietary habits and lifestyle needs to be considered for the prevention and development of an intervention for smartphone addiction among college students.